2009
DOI: 10.1016/j.ijgo.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-abdominal instillation of lidocaine during minor laparoscopic procedures

Abstract: Intraperitoneal instillation of lidocaine was effective in reducing postoperative pain after minor gynecological laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Although primary analysis showed a slightly steeper decreasing trend for the control group, it disappeared in multivariate longitudinal analysis while controlling for the analgesic use. This pattern of lidocaine is in line with the expected effects of lidocaine to appear at earlier hours and mainly on visceral pain (9,11,15,16). It has been shown that the effect may last even up to 3 days (15).…”
Section: Discussionsupporting
confidence: 82%
“…Although primary analysis showed a slightly steeper decreasing trend for the control group, it disappeared in multivariate longitudinal analysis while controlling for the analgesic use. This pattern of lidocaine is in line with the expected effects of lidocaine to appear at earlier hours and mainly on visceral pain (9,11,15,16). It has been shown that the effect may last even up to 3 days (15).…”
Section: Discussionsupporting
confidence: 82%
“…Our data support these studies and confirmed the limited duration of the local anesthetic effect with decreased narcotic use and pain scores on the day of surgery and the first postoperative day but no differences on the second postoperative day. Most previous studies included only minor gynecologic procedures such as tubal ligations, adhesiolysis, and adnexal procedures [19][20][21][22][23][24][25][26]. The results of our study as well as a study by Cruz et al [16] demonstrated that the superior pain control achieved with intraperitoneal administration of local anesthetic extends to patients undergoing minimally invasive hysterectomies and cancer staging procedures.…”
Section: Discussionsupporting
confidence: 63%
“…Long-acting local anesthetics have been shown to be efficient for postoperative pain relief in different types of laparoscopic procedures such as cholecystectomy [9] and appendectomy [10]. There are several studies showing conflicting results on the effect of LA instillation following gynecological laparoscopic procedures [10][11][12][13][14][15][16]. Timing of administration is of importance.…”
Section: Discussionmentioning
confidence: 99%